The effect of deformation on metastable pitting of 304 stainless steel in chloride contaminated concrete pore solution. (February 2016) - Feng, Xingguo; Lu, Xiangyu; Zuo, Yu; Zhuang, Ning; Chen, Da
Highlights: The lifetime and peak current density of individual metastable pits increase with increasing strains of up to 10%. Secondary metastable pitting always occurred in the severely deformed stainless steel sample in the chloride-contaminated pore solution. The growth rates of individual metastable pits are only modestly influenced by the strain level and carrier density, whereas the repassivation rates decrease dramatically with the two factors. Abstract: Metastable pitting of tensile-stressed 304 stainless steel in a simulated concrete pore solution was studied via potentiostatic polarization and Mott–Schottky plots. The results revealed that the carrier density of passive films increases significantly with increasing magnitude of the strain. In addition, the lifetime of metastable pitting increases with the strain and secondary metastable pitting always occurred in the severely deformed samples. The growth rates of individual metastable pits were only slightly influenced by the strain level and carrier density. However, the repassivation rates of pitting dramatically decreased with deformation and carrier density when the strain is below 10%.